Diplomasi Diaspora Cina Terhadap Hubungan Bilateral Amerika Serikat-Cina (2017-2021) - Imanniar Gadis Diandono; Adiasri Putri Purbantina (Intermestic: Journal of International Studies, 2022)
This article explores the phenomenon of diaspora diplomacy by China on bilateral relations between China and the United States in 2017-2021. Qualitative descriptive research and case study methods as well as the concept of diaspora in International Relations were used. Diaspora diplomacy is an instrument of public diplomacy to introduce the culture, ethnicity, and national identity of the country of origin to the host community. This article finds that the Chinese diaspora in the United States acts as a link between host and home countries, playing a role in strengthening economic ties. The activities of the Chinese diaspora through the Confucius Institute demonstrate the process of internationalizing culture, ethnicity, and national identity as a strategic communication tool that enhances bilateral relations between China and the United States. However, the current role of the Chinese diaspora has yet to demonstrate its peace-building function and provide an alternative political vision for its home country. Keywords: bilateral relations, China, diaspora diplomacy, United States